Demokratyzacja języka rosyjskiego i destrukcja kategorii stylistycznych na pocz. XIX i XXI wieku - Pieriewołoczanskaja, Swietłana (Studia Rossica Posnaniensia, 2010)
The process of language democratization happening in the broad context is culture democratization. This process often manifests itself in the attempt to release from strict, rigid norms. Stylistic confusion leads to appearance of synthesis, harmony of the middle style. The middle style appears as an invariant of styles, as “a substratum of a new literary language”. The quest for creative expression forms is provided with the aspiration to choosing expressive linguistic means. Phenomena of barbarization, vulgarization, deliberate pun verge on abnormality, opposition norm ↔ non norm.